Methane production from poultry waste; effect of different types of pre-treatment / Hazwani Hasmi, Asmida Ahmad and Faeiza Buyong - Hazwani, Hasmi; Ahmad, Asmida; Buyong, Faeiza (2016)
Anaerobic digestion (AD) of biomass is a well-established process to produce renewable energy, where organic matter is converted to biogas by microorganism. High solid content and complex structure of sludge-derived organic matter, methane production during digestion is limited at the hydrolysis step. Therefore pre-treatment of substrate is a way to accelerate the hydrolysis step. This study aimed to identify the optimum pre-treatment method to increase the methane production from poultry waste prior anaerobic digestion. The poultry waste was mixed with water, pre-treated, seeded with inoculums. Chemical and thermochemical pre-treatment were performed with NaOH and Ca(OH)2. The AD was conducted in bioreactors and incubated in water bath at 37 °C for 15 days. Results obtained show that the highest methane yield was at the thermochemical pre-treatment with Ca(OH)2 with cumulative amount of methane at 1665.17 ppm followed by chemical pre-treatment with Ca(OH)2, thermochemical pre-treatment with NaOH and chemical pre-treatment with NaOH with cumulative amount of methane at 1381.76 ppm, 884.07 ppm and 607.98 ppm respectively. Based on the comparison of the results, the thermochemical pre-treatment with Ca(OH)2 is the best pre-treatment as it produced the highest methane yield.